An exploration of the experiences of clients on antiretroviral therapy and their health care providers in KwaZulu Natal - Mhlongo, Euphemia Mbali (My University, 2011)
The aim of the study was to explore the practice of antiretroviral (ARV) therapy services, specifically regarding the patients’ issues and experiences, as well as the experiences of the health care providers rendering these services. Qualitative research methods were used, including a metasynthesis of qualitative research articles on human immunodeficiency virus (HIV) positive patients on ARV therapy, and phenomenological methods of inquiry. The study objectives were to conduct a metasynthesis of qualitative research on HIV-positive people on ARV therapy; to investigate the experiences of HIV-positive people who are on ARV therapy; to identify the constraints faced by HIV-positive people receiving ARV therapy; and to explore adherence to ARV therapy. The study was conducted in eThekwini district in KwaZulu Natal (KZN) province. The district was chosen considering the number of clinics rolling out ARV therapy. Three institutions initiating ARV therapy participated in the study; one urban, one semi-urban and one rural clinic, to ensure representation of each type. Participants were recruited from two initiating hospitals and one Community Health Centre providing ARV therapy. The metasynthesis revealed a shared set of four themes viz.: 1. Acceptance of, and coping with, HIV positive status 2. Social support and disclosure 3. Experiences and beliefs about HIV medication and health care 4. Provider relationships and health system factors Qualitative analyses of interviews with clients indicated their experiences and concerns, and were summarized in these themes: 1. Life before and after knowing HIV status 2. Initiating and continuing ARV therapy 3. Adherence to, and side effects of, the ARV therapy treatment 4. Social support for people on ARV treatment vi 5. Positive outcomes of being on ARV treatment 6. Improving access to ARV treatment services Analyses of in-depth interviews with health care providers specified their experiences, and were categorized into three themes viz.: 1. Establishing and maintaining a good client-provider relationship 2. Facilitators of and adherence to ARV treatment 3. Barriers to access to treatment
PhD, Faculty of Health Sciences, University of the Witwatersrand
Keywords: HAART; antiretroviral therapy; patient experiences; health care delivery